Architecture in the UK: a study in professional entry-routes and entry-gates. Issue 1 (30th April 2021) - Lester, Stan
Abstract : Purpose: This paper examines architecture as an example of the evolving context of qualifying routes in UK professions. Design/methodology/approach: The background and current state of architectural education, qualifying routes and regulatory frameworks in the UK is presented as a case-study, and compared with practices in professional education and qualifying more generally including the use of Degree Apprenticeships. Findings: Architecture has since the 1960s maintained an entry-route that is premised on periods of full-time academic study plus full-time practice. While a minority part-time version of this route has always existed (and is now being expanded through Degree Apprenticeships), variations seen in other professions such as experienced practitioner entry and accelerated routes from cognate fields have so far been lacking. Pressures for reform are emerging both from external changes affecting the profession and from the high cost of qualifying in relation to median incomes in the sector. Practical implications: There is a need for more flexible and less expensive routes to qualifying as an architect, with substantial scope to use practices from other professions and areas of higher education to recognise existing levels of competence and improve crossover with other design and construction fields. Originality/value: This is the first review of architectural qualifying requirements that has been made in the context of professional entry more generally.